A Feasible Solution for the Challenges Faced in Job Searching and the Recruitment Process - Loshith Samararathne; Kishara Dilshan; Chamaka Mendis; Thursha Herath; Dilshan De Silva; Piyumika Samarasekara (International Journal of Engineering and Management Research, 2022)
The competitive job market makes it difficult for people to find the best job opportunity that suits them well. A job seeker must apply for a considerably higher number of vacancies to at least be selected for an interview. There is no way for a job seeker to keep track of the application status, or to know the reason for rejections in the traditional application process. Not only job seekers but also recruiters face issues in the process as they receive many applications per day. There is a high chance for them to miss the most suitable candidates. This research paper aims to propose a web-based system to address the difficulties faced by both job seekers and job recruiters by analyzing the existing issues. The functionality of the proposed system will be based on four main components. Those components are considered user and inquiry management, vacancy management, application management, and assessments and interview management. User-friendliness and usability will be given priority in this proposed system.